PERANCANGAN LOGO DAN MEDIA PROMOSI PANTAI LUMBUNG TULUNGAGUNG MENGGUNAKAN TEKNIK FOTOGRAFI LANDSCAPE SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Mardha, Harel Laisa; Budiardjo, Hardman; Adrianto, Yosef Richo (Jurnal Art Nouveau, 2016)
The purpose of designing the logo and promotional media Lumbung Beach is to make a new tourist attraction in Tulungagung. The research was conducted with qualitative methods of doing interviews, documentation, observation and literature study to get the data used to support the manufacture of logo design concepts and media promotion. The concept in this study was obtained from the SWOT analysis, STP, and USP then the adjective derived dikerucutkan back so